Géoarchéologie de sites préhistoriques Le Gardon (Ain), Montou (Pyrénées-Orientales) et Saint-Alban (Isère) - Sordoillet, Dominique (Documents d'archéologie française, 2009)
In this work, Dominique Sordoillet accomplishes the difficult task of rendering a previously obscure discipline accessible to everyone. This work originates from her doctoral dissertation thesis, which received unanimous praise for its methodological and scientific rigor. Drawing on elements from the earth sciences, she studied the stratigraphy of three exemplary archaeological sites. The prehistoric sites of Gardon, Montou and Saint-Alban were thus subject to a precise micromorphological analysis, which considers a stratigraphy as a sedimentary record of time. Through a classification of the deposits into two large families based on their formation processes, she distinguishes the occupation facies, created by human activities, from the abandonment facies, which are characteristic of natural sedimentary and post-sedimentary processes. Based on these sedimentological data, replaced in their chronological and cultural contexts, she proposes different occupation scenarios and interpretations of the evolution of human activities, rituals and construction. This short, well illustrated presentation is written with a simple vocabulary and includes a glossary, all of which make it an effective tool for understanding the methods and objectives of micromorphology in the direct interest of field interpretations and methods.